Menggali Potensi Kearifan Lokal dalam Pembelajaran IPA: Peran Nilai Religius dalam Meningkatkan Pemahaman Konsep Mahasiswa - Fawaida, Ulya; Abidin, Zaenul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
This research was conducted with 50 students majoring in Science Education at IAIN Kudus. The objectives of this study were: 1) to identify local wisdom as a source of science education, 2) to analyze the integration of religious values in science education, and 3) to examine how the integration of local wisdom and religious values can enhance students' conceptual understanding. This study employed a mixed-methods approach. The findings revealed that the students utilized local potential and traditional knowledge as learning resources in science education. Moreover, the students integrated religious values such as responsibility, environmental concern, and preservation into their learning process. The integration of local wisdom and religious values in science education provided a contextual learning experience that presented a comprehensive understanding of natural phenomena and facilitated inquiry-based learning to construct students' multidisciplinary understanding. In conclusion, local wisdom in science education serves as a valuable learning resource that instills religious values and enhances students' conceptual understanding.